Genetic Deletion of Soluble Epoxide Hydrolase Attenuates Inflammation and Fibrosis in Experimental Obstructive Nephropathy. (22nd January 2015) - Chiang, Chin-Wei; Lee, Hsueh-Te; Tarng, Der-Cherng; Kuo, Ko-Lin; Cheng, Li-Ching; Lee, Tzong-Shyuan
Abstract : Soluble epoxide hydrolase (sEH) is abundantly expressed in kidney and plays a potent role in regulating inflammatory response in inflammatory diseases. However, the role of sEH in progression of chronic kidney diseases such as obstructive nephropathy is still elusive. In current study, wild-type (WT) and sEH deficient ( sEH −/− ) mice were subjected to the unilateral ureteral obstruction (UUO) surgery and the kidney injury was evaluated by histological examination, western blotting, and ELISA. The protein level of sEH in kidney was increased in UUO-treated mice group compared to nonobstructed group. Additionally, UUO-induced hydronephrosis, renal tubular injury, inflammation, and fibrosis were ameliorated in sEH −/− mice with the exception of glomerulosclerosis. Moreover, sEH −/− mice with UUO showed lower levels of inflammation-related and fibrosis-related protein such as monocyte chemoattractant protein-1, macrophage inflammatory protein-2, interleukin-1 β (IL-1 β ), IL-6, inducible nitric oxide synthase, collagen 1A1, and α -actin. The levels of superoxide anion radical and hydrogen peroxide as well as NADPH oxidase activity were also decreased in UUO kidneys of sEH −/− mice compared to that observed in WT mice. Collectively, our findings suggest that sEH plays an important role in the pathogenesis of experimental obstructive nephropathy and may be a therapeutic target for the treatment of obstructive nephropathy-related diseases.